Human Resources Identification in Ever Inactive Village-Owned Business Entities - Herlina, Herlina; S, Prayetno Agustinus; F, Nyayu Fadilah (Universitas Negeri Semarang, 2020)
This research to identify the condition of human resources in Village-Owned Business Entity (abbreviated as VOBE in this research) that ever inactive in West Tanjungjabung Regency . The method used in this research is survey with descriptive analysis. The result showed from 27 VOBE that were ever inactive in 2017, there are still 2 villages that haven't started to operate yet since they were built, due to passive administrators. Dominant businesses are service and trade. There was advantegous business unit in the VOBE, it didn’t prevent the VOBE to stop operating. The knowledge of VOBE management owned by respondents who are the village head and the head of VOBE was categorized as deficient. The motivation of the village head was in avarage category while the head of VOBE was persistence in the deficient level. The communication between respondents was categorized as adequate. Even though the head of village had avarage motivation, passable communication skill as the advisor, his knowledge was still minimum. The other obstacles for the village head was the head of VOBE was also having minimun knowledge about managing VOBE and also lack of motivation to run it.